Dibutyl phthalate disrupts conserved circadian rhythm in Drosophila and human cells. - Liu, W.; Cao, H.; Liao, S.; Kud?ak, B.; Williams, M.J.; Schiöth, H.B. (Science of the Total Environment, 2021)
People are constantly exposed to phthalates, due to their common use in the production of plastics, pharmaceuticals, cosmetics and skin care products. The ability of phthalates to disrupt endocrine signaling, leading to developmental, reproductive and metabolic defects, has been studied, yet how phthalates interfere with these biological functions is still unclear. To uncover DBP interacting molecular pathways, we raised Drosophila melanogaster on food containing dibutyl phthalate (DBP) at various concentrations. Whole transcriptome analysis of adult Drosophila reveals that DBP exposure throughout development disrupts the expression of genes central to circadian rhythm regulation, including increased expression of vrille (vri, human NFIL3), timeless (tim, human TIMELESS) and period (per, human PER3), with decreased expression of Pigment-dispersing factor (Pdf). DBP exposure also alters the expression of the evolutionarily conserved nuclear receptor Hormone receptor-like in 38 (Hr38, human NR4A2), which is known to regulate Pdf expression. Furthermore, behavioral assays determined that exposing Drosophila to DBP throughout development modifies the circadian rhythm of adults. Although DBP inhibits the expression of signaling systems regulating vision, including Rh5 and Rh6, two light-sensing G-protein coupled receptors involved in the daily resetting of circadian rhythm, it does not influence eye development. Circadian rhythm genes are well conserved from flies to humans; therefore, we tested the effect of DBP exposure on human breast cells (MCF10A) and demonstrate that, similar to the fruit fly model, this exposure disrupts circadian rhythm (BMAL1 expression) at doses that promote the proliferation and migration ability of MCF10A cells. Our results are the first to provide comprehensive evidence that DBP interferes with circadian rhythm in both adult Drosophila and human cells, which may help to explain the broad physiological action of phthalates.